Analisis Beban Kerja Fisik Pekerja Pabrik Kelapa Sawit di PT X Menggunakan Metode Cardiovascular Load (CVL) - Gunadi Priyambada; Jecky Asmura; Muhammad Reza; Anggi Safriyana; Widya Aryanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2023)
The palm oil industry is developing very rapidly in Indonesia, so the absorption of labor in palm oil factories has also increased. The demand to be able to produce Crude Palm Oil (CPO) optimally pushes the risk of physical work, especially at the sorting station. This study aimed to determine the effect of age, gender, and cigarette consumption on increasing workload using the Cardiovascular Load (CVL) method. This research was carried out by collecting pulse data for 8 workers using a pulse oximeter which was carried out before work (DNI) and while working (DNK). The results showing the level of physical workload on sorting workers using the CVL method found that 4 employees had a CVL percentage between 30% - 60%, namely having a moderate physical workload that required improvement. In comparison, the other 4 employees had a CVL percentage <30%, namely no significant loading occurs. The energy consumption expended by sorting workers is ±107 Kcal/hour.